OPTIMIZATION OF ACUTE AND RECURRENT STREPTOCOCCOSIS THERAPY AMONG CHILDREN - E.A. Krasnova; A.V. Vasyunin (Педиатрическая фармакология)
The researchers examined 56 children aged between 3 and 12 years old, suffering from acute tonsillitis caused by group A β-hemolytic streptococcus. After the antibacterial therapy of 10 days long all the children were divided into 2 groups. The first group comprised 30 children, who received the medication of the bacterial lysate (imudon, solvay pharma, Germany). The length of the medication intake was 14 days. The children of the second group (26 children) underwent one-time injection of bycillin. The research findings showed that application of the bacterial lysate drastically increased the efficiency of therapy and improved the contents of pharynx microflora within the decubation of acute tonsillitis caused by group a hemolytic streptococcus.Key words: acute tonsillitis, group A β-hemolytic streptococcus, treatment.